Efficacy of Lumboperitoneal Shunting in Patients with Normal Pressure Hydrocephalus - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2016)
AIM: To evaluate the effectiveness of lumboperitoneal (LP) shunt procedures in the treatment of normal pressure hydrocephalus (NPH). MATERIAl and METHODS: A medical record review was conducted to obtain demographic, clinical, laboratory data, as well as pre-, intra, -postoperative details of 65 patients who underwent LP shunt surgery for NPH between January 1, 2001 and January 1, 2014 in the Neurosurgery Clinics of Ankara Training and Research Hospital and Ankara Numune Hospital. RESULTS: At the 3rd month after LP shunt surgery, headache was resolved in almost all patients. At the end of first year, while statistically significant improvements were noted in the Modified Rankin Scale Scores and Mini-Mental State Examination Scores, gait disturbance, urinary incontinence and cognitive functions were improved by 86%, 72% and 65% of the patients, respectively. CONCLUSION: LP shunt surgery is associated with a lower rate of complication in comparison to ventriculoperitoneal shunt surgery and is an effective procedure in the treatment of NPH.
Keywords: Lumboperitoneal shunt; Normal pressure hydrocephalus; Cerebro-spinal fluid; COMPLICATIONS; MIGRATION; CATHETER